Discrete element modelling of wellbore integrity in high temperature geothermal reservoirs: - TerHeege, J.H.; Orlic, B.; Wollenweber, J. (American Rock Mechanics Association (ARMA), 2017)
Geothermal drilling environments are often hostile to well materials, especially in magmatic settings where properties of well casing and cements may rapidly change as a result of high temperatures and chemically active formation fluids. Prolonging the lifetime of such geothermal wells is one of the key challenges to achieve a commercially successful geothermal projects. This study aids analysis of critical stress conditions for well integrity and initiation of damage in wellbore cement during operation of geothermal wells using a combination of analytical and discrete element models. The analytical models are used to determine wellbore stresses that are applied to 3D discrete element models of typical well sections. Wellbore models and boundary conditions are based on subsurface conditions encountered in well IDDP-1 of the Iceland Deep Drilling Project. Possibilities of using the discrete element models to test the behavior of well materials under realistic pressure and temperature conditions in this type of wells are explored. The workflow may be used to test novel well materials and designs at different depths.